Physical Models of Semiconductor Quantum Devices - Fu, Ying.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The science and technology relating to nanostructures continues to receive significant attention for its applications to various fields including microelectronics, nanophotonics, and biotechnology. This book describes the basic quantum mechanical principles underlining this fast developing field. From the fundamental principles of quantum mechanics to nanomaterial properties, from device physics to research and development of new systems, this title is aimed at undergraduates, graduates, postgraduates, and researchers.
Semiconductor materials -- Electronic processes in semiconductors -- Optical properties of semiconductors -- Nano-size electronic devices -- Quantum optoelectronics -- Plasmonics -- Numerical recipes.
Keywords: Physics; Chemistry; Optical materials; Physics; Nanoscale Science and Technology; Optical and Electronic Materials; Theoretical and Computational Chemistry